2018
DOI: 10.1088/1361-6528/aad0b7
|View full text |Cite
|
Sign up to set email alerts
|

Noise spectroscopy of tunable nanoconstrictions: molecule-free and molecule-modified

Abstract: Devices with metallic nanoconstrictions functionalized by organic molecules are promising candidates for the role of functional devices in molecular electronics. However, at the moment little is known about transport and noise properties of nanoconstriction devices of this kind. In this paper, transport properties of bare gold and molecule-containing tunable cross-section nanoconstrictions are studied using low-frequency noise spectroscopy. Normalized noise power spectral density (PSD) S /I dependencies are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…As shown in Figure c,d, the regions with low or high charge trap density correspond mostly to those of CNT bundles or individual CNTs , respectively. The scaling behavior of σ ∝ N T –1 in the CNT bundle regions can be explained by the ballistic transport as reported previously. , Briefly, the current-normalized noise PSD can be written by a Hooge’s equation like where α H , Δ N , e , v , R , and V are the Hooge’s parameter, the number of carriers in a segment Δ x Δ y , an electric charge, a characteristic carrier velocity, the resistance of a segment Δ x Δ y , and an applied bias at a segment Δ x Δ y , respectively. In the case of a ballistic transport, the carrier velocity v corresponds to the thermal velocity .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…As shown in Figure c,d, the regions with low or high charge trap density correspond mostly to those of CNT bundles or individual CNTs , respectively. The scaling behavior of σ ∝ N T –1 in the CNT bundle regions can be explained by the ballistic transport as reported previously. , Briefly, the current-normalized noise PSD can be written by a Hooge’s equation like where α H , Δ N , e , v , R , and V are the Hooge’s parameter, the number of carriers in a segment Δ x Δ y , an electric charge, a characteristic carrier velocity, the resistance of a segment Δ x Δ y , and an applied bias at a segment Δ x Δ y , respectively. In the case of a ballistic transport, the carrier velocity v corresponds to the thermal velocity .…”
Section: Resultsmentioning
confidence: 77%
“…The scaling behavior of σ ∝ N T –1 in the CNT bundle regions can be explained by the ballistic transport as reported previously. , Briefly, the current-normalized noise PSD can be written by a Hooge’s equation like where α H , Δ N , e , v , R , and V are the Hooge’s parameter, the number of carriers in a segment Δ x Δ y , an electric charge, a characteristic carrier velocity, the resistance of a segment Δ x Δ y , and an applied bias at a segment Δ x Δ y , respectively. In the case of a ballistic transport, the carrier velocity v corresponds to the thermal velocity . Thus, the normalized PSD can be described as where T and m e are the temperature and the mass of an electron, respectively.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Flicker noise of the molecule‐free and the molecule‐containing bare junctions were also investigated by the MCBJ technique, and this indicated that the noise level decreased in the ballistic regime of conductance after the modification of the molecule (1,4‐benzenedithiol, BDT). [ 50 ] The results of these reports are valuable for improving the basic knowledge of the development of flicker noise in molecular junctions.…”
Section: Progress In the Characterization Of Electronic Noise In Molementioning
confidence: 99%
“…
challenging to reveal the evolution of the charge transport mechanism from the conductance characterization of singlemolecule conductance. In the past decade, numerous data analysis methods were introduced to process the conductance traces, including statistical methods, [4][5][6][7] analytical modeling, [8,9] electronic noise analysis, [10][11][12][13][14][15] and machine learning and deep learning methods. [16][17][18] Among these methods, analysis of flicker noise from the single-molecule junctions has suggested to shed new light on the understanding of charge transport mechanisms of singlemolecule junctions.
…”
mentioning
confidence: 99%